Khalwat dan Relevansinya Terhadap Pendidikan Islam - romlah romlah; Sanuri Sanuri (Jurnal Pendidikan Educandum, 2022)
The meaning of khalwat in a language that is to escape from the crowd and leave all activities for 40 days in the forest. The purpose of the origin of khalwat is to worship God so that he can have intelligence and purity of the soul. This paper is the result of research based on reliable sources, namely K.H Buya Syakur and the idea of thinking about the benefits of Khalwat. Khalwat has a relationship with one of the objectives of Islamic education. Namely increasing intellectual and spiritual intelligence for humans, With khalwat, then one of the solutions in realizing the goals of national education in totality. Namely pious with many good deeds of noble ethics, generous in sharing sustenance, virtuous in acting, and wise in making decisions.